Freedom incorporated anticommunism and Philippine independence in the age of decolonization - Woods, Colleen (Ithaca, New York Cornell University Press, 2020)
"Freedom Incorporated tells the story of American and Filipino anticommunists who sought to turn the Philippines into a laboratory for exportable models of decolonization, postcolonial statehood, and anticommunist warfare"-
Introduction : A Decolonized Empire -- An Amazing Record of Red Plotting : Policing Radical and Racial Boundaries in the Colonial Philippines -- State Violence and the Problem of Political Legitimacy : WWII, Philippine Independence, and the Hukbalahap -- The Anti-Communist International : The Philippine Front and Global Anticommunist Warfare -- Efficient, Honest, and Democratic : US Foreign Aid, Public Administration, and the Campaign Against Corruption -- A Dirty, Half-Hidden War : The CIA and US-Philippine Covert Operations in Southeast Asia -- Epilogue : A Friendship Written in Blood.
Includes bibliographical references and index.
Keywords: Anti-communist movements -- Philippines; Anti-imperialist movements -- Philippines; Decolonization -- Philippines; Postcolonialism -- Philippines; Philippines -- Politics and government -- 20th century; United States -- Foreign relations -- Philippines; Philippines -- Foreign relations -- United States